Audio-Visual Materials in an Integrated Literacy-Mechanical Skills Training Program for Young Unemployed Adults - Orest Cap; Odarka S. Trosky; Barbara Wynes; Robin Cutts (The Canadian Network for Innovation in Education (CNIE), 1986)
This article describes how audio-visual materials were selected and used for a group of thirty unemployed young adults, ranging in ages (17-21), attending an integrated literacy-mechanical skills program. This program consisted of an initial two months of class activities followed by approximately seven months in the field and a final two weeks in class. The audio-visual materials which met Vander Meer's (1973) criteria of appropriateness, to reflect the curriculum and to elicit expected and desired behavior in the learner, were selected on the basis of the Von Mondfrans and Houser six step paradigm (1973) to relate to performance-based objectives. The selected materials did not necessarily reflect the very best nor the most recent in the field, rather they represented the best and most recent from those readily available. Evaluation through questionnaires, reports, observations and participant comments indicated that the audio-visual materials used in the program closely related to the three main functions of audio-visual materials in vocational instruction.